Accuracy, Confidence, and Experiential Criteria for Lie Detection Through a Videotaped Interview - Curci, Antonietta; Lanciano, Tiziana; Battista, Fabiana; Guaragno, Sabrina; Ribatti, Raffaella Maria (Frontiers in Psychiatry, 2019)
The individuals’ ability to discriminate lies from truth is far from accurate, and is poorly related to individuals’ confidence in his/her detection. Both law enforcement and non-professional interviewers base their evaluations of truthfulness upon experiential criteria including emotional and expressive features, cognitive complexity, and paraverbal aspects of interviewees’ reports. The current experimental study adopted two perspectives of investigation: The first is aimed at assessing the ability of naïve judges to detect lies/truth by watching a videotaped interview; the second takes into account the interviewee’s detectability as a liar or as telling the truth by a sample of judges. Additionally, the study is intended to evaluate the criteria adopted to support lie/truth detection and relate them with accuracy and confidence of detection. Results showed that judges’ detection ability was moderately accurate and associated with a moderate individual sense of confidence, with a slightly better accuracy for truth detection than for lie detection. Detection accuracy appeared to be negatively associated with detection confidence when the interviewee was a liar, and positively associated when the interviewee was a truth-teller. Furthermore, judges were found to support lie detection through criteria concerning emotional features, and to sustain truth detection by taking into account the cognitive complexity and the paucity of expressive manifestations related with the interviewee's report. The present findings have implications for the judicial decision on witnesses’ credibility.